Standards as epistemological practice. A study of how Danish school leaders use assessment findings in the development of leadership practice - Søren Hornskov; Camilla Nørgaard; Pernille Hansen (Taylor & Francis Group, 2019)
During recent years, we have seen an increase in the complexity of school leadership as knowledge work. The new forms of knowledge available to school leadership, such as performance data and survey-based data, raise the expectation that leaders make relevant use of these knowledge resources. Theory and policy claim that new knowledge is of instrumental use in leadership decision making, yet there are important limitations to this strand of efficiency thinking. The paper analyzes leaders' use of organizational assessment data for the purposes of developing their leadership practice. The paper constructs this empirical object as a composite of general quality standards and specific knowledge about each school. Accountability practices are taken to be specific to particular schools and professional organizations. The paper explores how school leadership practices can be researched as an interplay between quality standards emerging from abstracted knowledge ressources such as theory and strategy, and local knowledge work. It may be difficult to balance these forms of knowledge work, and that may explain why leaders often find it hard to use new knowledge resources. The task of making sense of the flow of knowledge and new standards becomes a complex, comprehensive and time-consuming part of practical leadership.